KAJIAN PENERIMAAN PORTAL INTRANET KOMINFO BERDASARKAN KONSEP TECHNOLOGY ACCEPTANCE MODEL (TAM) DI BPPKI JAKARTA - Kautsarina, Kautsarina (Masyarakat Telematika Dan Informasi : Jurnal Penelitian Teknologi Informasi dan Komunikasi, 2012)
Implementasion of intranet portal has been running, including in BPPKI Jakarta but has yet to be evaluated , which is actually necessary, especially in the presence of new technologies by users. This study aimed to assess the acceptance of intranet portal in BPPKI Jakarta using Technology Acceptance Model (TAM) approach, so as to know the factors that influence the acceptance of intranet portals BPPKI Kominfo in Jakarta. This research is a quantitative research through a questionnaire with Likert scale made to all employees who have an identity on intranet portal. The results showed that only 35% ofrespondents who use intranet portal, and based on hypothesis testing found that the interest in the use of an intranet portal has a significant positive effect on the use of intranet portals.